Directly Confirming the Z1/2 Center as the Electron Trap in SiC Through Accessing the Nonradiative Recombination. Issue 2 (14th November 2021) - Gu, Yuxiang; Shi, Lin; Luo, Jun-Wei; Li, Shu-Shen; Wang, Lin-Wang
Abstract : SiC is an important wide‐bandgap semiconductor for high‐power electronics and high‐temperature applications. Its Z 1/2 center, recognized as a carrier lifetime killer, has been extensively studied as it is a key issue impeding many applications of SiC. It is well established that the Z 1/2 center originates from carbon vacancies (VC ), but direct access to the microscopic mechanism underlying its nonradiative recombination process is lacking. Herein, to consolidate such identification, the multiphonon‐assisted nonradiative recombination rates of previously proposed different candidates of the Z 1/2 center are evaluated by performing first‐principles calculations. The calculated electron transition cross sections of the VC ( σ n = 2.5 × 10 − 15 cm 2 at the k‐site and σ n = 3.4 × 10 − 15 cm 2 at the h‐site) are in accordance with the experimental values [from σ n = 3.0 × 10 − 15 cm 2 to σ n = 1.0 × 10 − 14 cm 2 ] for the Z 1/2 center. However, all of the other candidates are orders of magnitudes smaller in transition cross sections. This provides further evidence that the carbon vacancy (VC ) is the Z 1/2 center from the electron transition cross sections. However, it is also found that the hole transition cross sections of the VC are very small. Various hypotheses are provided to consolidate this fact with the conclusion that Z 1/2 is the carrier lifetime killer. Abstract : The calculated electron‐capturing cross sections of the carbon vacancy (VC ) reasonably agree with the experimental values of the non‐radiative recombination center Z 1/2 . However, the other previously considered candidates have orders of magnitudes smaller in transition cross sections. From the comparison of the electron‐capturing cross sections, it is confirmed that the VC defect is indeed responsible for the Z 1/2 center observed in the experimental spectrum.